Agronomics of teff - Assefa, Kebebew; Chanyalew, Solomon (International Food Policy Research Institute, 2018)
This chapter gives an overview of the agronomics of teff primarily focusing on the major biophysical aspects of the teff plant and its husbandry in Ethiopia. The first section elaborates on the major peculiar features that constitute the reasons for the sustained extensive cultivation of the crop in Ethiopia. An understanding and appreciation of the relative merits of the crop in cultivation and use are vital for government policy makers, researchers, development partners and donors, and the public at large for agrarian transformation in Ethiopia to be achieved. Notably, the focus on research and development of teff has given rise to considerable attention of this crop’s significance and meritorious features. In the subsequent sections, other salient aspects are covered, including brief insights into the genetic resources to improve the crop, the improved varieties released so far, and the agronomic and pest management methods used in teff husbandry. The chapter concludes with a summary of the practical implications of the major issues covered, followed by remarks on the prospects of teff research and development in Ethiopia.